GBL UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR MATERI MENGENAL AKUN BELAJAR.ID DALAM BIMBINGAN TIK - Yuni Tri Supanti; Rahmat Mulyono (STKIP Subang, 2022)
This research is aimed to improve students learning activity and achievement through introducing belajar.id account at the eight grade students of SMP N 19 Purworejo by using Game Based Learning. This research show 85% of students gained the average score of 75, the percentage of students activity reach 80% . This student’s activity categorized good. This research is conducted on March to May of 2021, on the second semester at the eight grade students of SMP N 19 Purworejo in the academic year of 2021/2022. This research is conducted on VIII C students of SMP N 19 Purworejo which consist of 32 students (male and female). The techniques of collecting data used in this research are observation and test. The collected data is analyzed descriptively by using percentage analysis. The steps used in this research are as follow: 1) planning, (2) acting, (3) observing and evaluating, and 4) reflecting and follow –up. This class action research activity is carried out in 2 cycles, namely cycle I and cycle II. The result of the research shows that there is a enhancement in stuedents learning activity. It can be seen from data observation/monitoring of student learning activities. On cycle I, the average students activity obtained 80,21%. On cycle II , It is increased to 83,51 %. This research shows that there is a enhancement in students learning achievement in knowing belajar id. account. Before this reasearch is conducted, the students only obtained the average score 66,25 , with a classical learning mastery of 40.63%. However, students can obtain the average score 76,49 in cycle I, with a classical learning mastery 66,50 %. Then students can obtain the average score 87,11 in cycle II, with a classical learning mastery 96.88 %. The result of this reaserach show that there is a increasing positive students behaviour in learning belajar id account . In the first cycle, the change of student behavior towards postitive is 81.43% and in the second cycle, it is increased to 82.99%. The result of this research shows that there is an increase in students activity and students learning achievement as well as changes of student behavior towards positive in learning belajar.id accounts at eight grade (VIII C) students of SMP Negeri 19 Purworejo through Game Based Learning learning.